A review of ixekizumab in the treatment of psoriatic arthritis. (2nd December 2018) - O'Rielly, Darren D.; Rahman, Proton
ABSTRACT: Introduction : Psoriatic arthritis (PsA) is a heterogeneous inflammatory disorder with articular, peri-articular, and extra-articular features along with selected co-morbidities as a sequela to chronic inflammation. There is accumulating evidence that the Th-17 signaling pathway is of critical importance in PsA pathogenesis. Areas covered : Ixekizumab (IXE) is a humanized immunoglobulin G subclass 4 (IgG4) monoclonal antibody directed against IL-17A. Two phase III randomized clinical trials, SPIRIT-P1 and SPIRIT-P2, unequivocally demonstrated superiority of IXE (80 mg every two or 4 weeks) dosing over placebo in moderate-to-severe PsA patients that failed either NSAIDs, conventional disease-modifying anti-rheumatic drugs (csDMARDs), or tumor necrosis factor-α inhibitors (TNFi) for numerous articular and cutaneous parameters. IXE also delayed structural progression of PsA. No new safety signals were identified as compared with chronic plaque psoriasis studies which included many more patients. Expert opinion : IXE is a highly effective treatment for moderate to severe PsA patients, including those that have been previously exposed to csDMARD and TNFi. Most domains of PsA significantly improved with IXE treatment and disease modification was achieved.